Local Dynamics of the Hydration Water and Poly(Methyl Methacrylate) Chains in PMMA Networks - Fujii, Yoshihisa; Tominaga, Taiki; Murakami, Daiki; Tanaka, Masaru; Seto, Hideki (Frontiers in Chemistry, 2021)
Dynamic behavior of polymer chains and water molecules in a system with tiny amount of water molecules hydrated at poly(methyl methacrylate) (PMMA) matrix was investigated. It has been known that polymeric materials exhibit a hierarchical dynamics from sub-molecular scales to collective segmental relaxations and chain diffusion. With respect to such a hierarchy of dynamics, water molecules have been widely recognized as plasticizers that activate the segmental motion of polymer chains from the evidence of the decrease of the glass transition temperature. Herein, combined with judicious hydrogen / deuterium labeling, we conduct quasi-elastic neutron scattering (QENS) experiments on PMMA for dry and hydrated states. The results clearly indicate that the dynamics of polymer chains is accelerated and the slower water molecules than the bulk water exist. It is suggested that hydration water affect the local motion of the functional groups of PMMA and activate the local relaxation process called hindered rotation which is widely accepted to be generally insensitive to a change in the microenvironment.